Pancasila As A Paradigm For The Development Of Legal Science - Junaedi Junaedi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research explores the role and relevance of Pancasila and the 1945 Constitution in facing the challenges of globalization and the multidimensional crisis in Indonesia. Using qualitative methods, this study highlights the need for legal reform to follow the paradigm of legal development, with the main question of whether Pancasila can be the main foundation of legal development. The research findings show that there is disorientation in applying Pancasila values, but Pancasila-based education strategies can be an effective solution. Challenges faced include political and ideological barriers, but there are opportunities to increase awareness and integration of Pancasila values in legal education and practice. This research confirms that Pancasila as a paradigm for the development of legal science plays an important role in shaping the character of citizens, ensuring justice and welfare in accordance with the 1945 Constitution. The results emphasize the need for a comprehensive approach to legal education that integrates Pancasila values, as well as cooperation between legal practitioners, policymakers, and civil society. The integration of Pancasila values is considered key to ensuring that the law reflects the nation's identity and acts as an instrument of inclusive and equitable development. as for the purpose of this study aims to analyze how the two principles can be used as a foundation in dealing with changes and resolutions.